"Vitamin D Deficiency Is More Common in Women with Autoimmune Thyroiditis: A Retrospective Study". (18th August 2021) - Turashvili, Nino; Javashvili, Lali; Giorgadze, Elene
Abstract : Background . Vitamin D is a hormone that is mainly produced in the skin upon ultraviolet B radiation exposure and has important influence on various organs. In recent years, data have been collected that vitamin D deficiency plays an important role in the development of various nonskeletal diseases, including autoimmune diseases. Chronic autoimmune thyroiditis (Hashimoto's thyroiditis) is one of the most common organ-specific autoimmune endocrine diseases. It is characterized by increased level of antithyroid peroxidase and/or antithyroglobulin antibodies in blood, which often leads to thyroid dysfunction and structural changes of the gland. There is an opinion that vitamin D deficiency may be considered as an important risk factor for development of chronic autoimmune thyroiditis, but data of various small studies are controversial. Despite the fact that Georgia is a sunny country, vitamin D deficiency is a widespread problem here. Thyroid diseases, including the chronic autoimmune thyroiditis, are also very common in Georgia. The aim of our research was to compare the level of vitamin D between the patients with chronic autoimmune thyroiditis and the healthy subjects. Methods . This retrospective study enrolled subjects, who were 18–70 years old and visited the clinics "Cortex" and "National Institute of Endocrinology" in 2018 or in 2019 from mid-spring to mid-summer. Data of thyroid-stimulating hormone, free thyroxine, antithyroid peroxidase antibodies, antithyroglobulin antibodies, thyroid ultrasonography, and 25(OH) vitamin D were retrospectively analysed based on medical history. In total, data of 1295 patients were collected. The statistical processing of data was performed through the SPSS 20 program. Results . The negative association between thyroid-stimulating hormone, antithyroid peroxidase antibodies, antithyroglobulin antibodies, heterogeneous parenchyma of thyroid gland, and vitamin D was found in women. Statistically significant association was not detected in men. Conclusions . Serum vitamin D is lower in women with autoimmune thyroiditis and primary hypothyroidism. Further studies are needed to evaluate the influence of vitamin D supplementation on thyroid autoantibody positivity or primary hypothyroidism.